The paradoxical injunctions of partnership in care: Patient engagement and partnership between issues and challenges - Khayreddine Bouabida; Marie-Pascale Pomey; genevieve Cyr; Ursulla Aho-Glele; Breitner Gomes Chaves (The Beryl Institute, 2021)
Partnership in care and patient engagement is an expanding approach and tremendously promising for improving the quality of healthcare services. However, the approach could be subject to many issues and challenges of various kinds. In this paper, we develop a reflection of the challenges and issues that the approach of patient engagement and partnership in care is facing. After a brief presentation of certain key concepts of partnership in care and patient engagement, we discuss in this paper the most worthy of consideration issues that we identified and classified as follows: Political, Financial, Organizational, Clinical, and Ethical Issues. We then conclude the paper with certain recommendations that may help to better deal with those challenges and issues and alleviate their impacts. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.